Myomectomy for Multiple or Giant Uterine Fibroids - Hiramatsu, Yuji (The Surgery Journal, 2020)
Myomectomy for diffuse leiomyomatosis and giant fibroid exceeding 30 cm in length is a particularly difficult operation. For diffuse leiomyomatosis, what kind of incision is put in and nucleated, how to suture the wound is a problem. In the case of giant fibroids, the degree of difficulty varies greatly depending on the site, size, and number of fibroid. The points should be taken into account at the time of surgery are as follows: (1) how to incision because incision becomes long, (2) how to remove multiple fibroids together, reduce incisional wounds, and reconstruct the uterus, (3) how to reduce the bleeding, how to suture not to leave a dead space. From the preoperative magnetic resonance imaging findings for each case, we will conduct surgery as far as possible to simulate, but, in fact, it is necessary to judge instantaneously at the time of laparotomy. It is necessary to see many difficult operations and acquire the judgment ability.
Keywords: myomectomy; diffuse leiomyomatosis; giant fibroid; cervical fibroid